Réponses

2014-10-23T18:01:52+02:00
Bonsoir

x + 3 y = 2
4 x +10 y = 10

dans la 1ere équation

x = 2 - 3y

tu remplaces cette valeur dans la 2ème équation

4( 2 - 3y) + 10y = 10
8  - 12 y + 10y = 10
- 2 y = 10 -8
- 2y = 2
y = - 1

x - 3 = 2
x = 2 +3
x = 5

tu vérifies
x + 3y = 2
5 - 3 = 2
2 = 2

  • Utilisateur Brainly
2014-10-23T18:02:53+02:00
X + 3y = 2
4x + 10y = 10

x = 2 - 3y

4(2 - 3y) + 10y = 10
8 - 12y + 10y = 10
- 2y = 2
y = - 1

4x + 10 * (- 1) = 10
4x = 10 + 10
4x = 20
x = 5

S= {- 1 ; 5}